Incidence and risk factors of acute kidney injury in severely burned patients in Mulago Hospital, Uganda - a prospective cohort - Wandabwa, Joel; Kalyesubula, Robert; Najjingo, Irene; Nalunjogi, Joanitah; Ssekitooleko, Badru; Mbiine, Ronald; Alenyo, Rose (International Journal of Burns and Trauma, 2022)
Acute Kidney Injury (AKI) is associated with increased mortality among severely burned patients. According to World Health Organization (WHO) 11 million people suffer from burns worldwide and burns contribute to 180,000 deaths yearly. Majority of these burns occur in the Low and Middle-Income Countries. Currently there is no published data on the incidence, risk factors and outcomes of AKI among patients with severe burns in Uganda. Early screening and treatment of patients at risk of developing AKI has been shown to improve survival. We therefore carried out a study to determine the incidence and risk factors of AKI in Uganda. Methods: This was a prospective cohort study that consecutively included patients with severe burns admitted in Mulago National Referral Hospital burns unit between February and May 2018. Patients were followed up for 14 days and AKI was assessed according to the KIDGO criteria. The incidence of AKI was expressed as a proportion. Kaplan Meier graph was used to estimate the median survival of patients with or without AKI. The risk factors for AKI were assessed using cox proportion hazard regression analysis. Results: Of the 147 patients screened, 92 met the inclusion criteria but 2 declined to participate in the study. Of the study participants, 48 (53.3%) were male, 47 (52.2%) were aged 3 years and below, the median TBSA was 17 (IQR; 13-23), 58 (69.9%) had low albumin levels and 16 (18.6%) had inhalation burns. The incidence of AKI was found to be 34.4% (95% CI; 25.9-45.9) with a mortality of 11.76% (95% CI; 6.37-20.73). Total burn surface area HR=3.10 (95% CI; 1.39 to 6.94 P=0.003) was the only independent risk factor for AKI. Conclusion: The incidence and mortality rate of AKI in patients with severe burns was found to be high. Having burns greater than 18% TBSA was an independent risk factor for AKI. Therefore, patients with burns greater than 18% should be assessed regularly for AKI so that treatment is instituted early should it occur.
Keywords: AKI; Incidence; Risk factors